A cohort of Indigenous Australian women and their children through pregnancy and beyond: the Gomeroi gaaynggal study. (15th April 2016) - Ashman, A. M.; Collins, C. E.; Weatherall, L.; Brown, L. J.; Rollo, M. E.; Clausen, D.; Blackwell, C. C.; Pringle, K. G.; Attia, J.; Smith, R.; Lumbers, E. R.; Rae, K. M.
Abstract : Indigenous Australians have high rates of chronic diseases, the causes of which are complex and include social and environmental determinants. Early experiences in utero may also predispose to later-life disease development. The Gomeroi gaaynggal study was established to explore intrauterine origins of renal disease, diabetes and growth in order to inform the development of health programmes for Indigenous Australian women and children. Pregnant women are recruited from antenatal clinics in Tamworth, Newcastle and Walgett, New South Wales, Australia, by Indigenous research assistants. Measures are collected at three time points in pregnancy and from women and their children at up to eight time points in the child's first 5 years. Measures of fetal renal development and function include ultrasound and biochemical biomarkers. Dietary intake, infant feeding and anthropometric measurements are collected. Standardized procedures and validated tools are used where available. Since 2010 the study has recruited over 230 women, and retained 66 postpartum. Recruitment is ongoing, and Gomeroi gaaynggal is currently the largest Indigenous pregnancy-through-early-childhood cohort internationally. Baseline median gestational age was 39.1 weeks (31.5–43.2, n =110), median birth weight was 3180 g (910–5430 g, n =110). Over one third (39.3%) of infants were admitted to special care or neonatal nursery. Nearly half of mothers (47.5%) reported tobacco smoking during pregnancy. Results of the study will contribute to knowledge about origins of chronic disease in Indigenous Australians and nutrition and growth of women and their offspring during pregnancy and postpartum. Study strengths include employment and capacity-building of Indigenous staff and the complementary ArtsHealth programme.